A Review of Biologic Therapies Targeting IL-23 and IL-17 for Use in Moderate-to-Severe Plaque Psoriasis. Issue 1 (March 2016) - Campa, Molly; Mansouri, Bobbak; Warren, Richard; Menter, Alan
Abstract The development of several highly effective biologic drugs in the past decade has revolutionized the treatment of moderate-to-severe plaque psoriasis. With increased understanding of the immunopathogenesis of psoriasis, the emphasis has turned toward more specific targets for psoriasis drugs. Although the complex immunological pathway of psoriasis is not yet completely understood, current models emphasize the significant importance of interleukin (IL)-23 and IL-17. Several biologic drugs targeting these cytokines are now in various stages of drug development. Drugs targeting IL-23 include BI-655066, briakinumab, guselkumab, tildrakizumab, and ustekinumab. Drugs targeting IL-17 include brodalumab, ixekizumab, and secukinumab. While many of these have shown safety and good efficacy in clinical trials of moderate-to-severe plaque psoriasis, long-term safety is still to be established.